Third Annual Conference of the Parliamentary Network on the World Bank, Bern, May 9-11, 2002 : Keynote Speeches - Wolfensohn, James D.; Wade, Abdoulaye; Moore, Mike (2016)
On May 9-11, 2002 the members of the Parliamentary Network on the World Bank (PNoWB) met in Bern, Switzerland for their Third Annual Conference. The meeting took place in the Swiss Parliament to mark the tenth anniversary of Swiss membership in the Bretton Woods institutions. The attendance of 104 Members of Parliament from 42 countries helped to firmly establish the Parliamentary Network of the World Bank (PNoWB) as a parliamentary sounding board. The meeting underscored the important role that Parliamentarians play in international development. In the various sessions of the conference two themes recurred: implementation and governance. The participants of the conference were challenged by World Bank President James Wolfensohn to focus on implementing the international consensus that emerged from the conferences in Doha and Monterrey and leading up to Johannesburg. He urged Parliamentarians to invest in their relationships with their governments to be able to play an active role in implementing these development initiatives. At the same time, participants discussed the role that Parliamentarians could play to strengthen governance structures in developing countries to create an environment conducive to the success of development policies.